Modification of cognitive behavior therapy to improve the skill of elderly with osteoarthritis - Rizkiyani Istifada; Etty Rekawati; Widyatuti Widyatuti (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2021)
One of the characteristics of physical changes in the elderly involves a decrease in the musculoskeletal system, such as the depletion of the synovial joint fluid which has an impact on the pain felt in joints. This condition can cause a disruption of the quality of life for the elderly and results in increases in the family burden. The purpose of cognitive-behavioral therapy in nurse care planning is to provide an overview of the implementation of family care nursing, community care health nursing, and management of health services by community health nurses to the elderly with osteoarthritis. The innovation and development of this senior citizen community program, initially named Lansia SMART (SMART Elderly), consists of six sessions, including psychoeducation sessions, cognitive restructuring sessions, pain management sessions with progressive muscle relaxation, activity scheduling sessions, problem-solving sessions, and tutorial sessions for the Lansia SMART (SMART Elderly) group with the Android application. The final maintaining challenging stage of these services involved 59 elderly participants. Data analysis used paired T-tests. The results of this innovation showed significant differences in the behavior of the elderly participants after the implementation of the SMART Elderly program (p < 0.05). The SMART Elderly program was effective to improve the elderly participants’ behavior. Nurses can use cognitive behavioral therapy to improve the process of self-management of osteoarthritis among their clients.